Position-Sensitive Detector in Neutron Tomography and Material Characterization. (16th November 2020) - Idris, Faridah Mohamad; Murshidi, Julie Andrianny; Mohamed, Abdul Aziz; Ashari, Norabidin; Yazid, Khairiah; Azman, Azraf; Wan Abdullah, Wan Ahmad Tajuddin; Norjoharuddeen, Nurfikri; Baijan, Abdul Halim; Sabri, Rokiah; Mohd Zin, Mohd Faiz
Abstract: Position-sensitive detectors (PSDs) have been used in neutron tomography and nanostructural characterization of material using neutrons that scattered from a monochromator of highly oriented pyrolytic graphite type, placed directly in the neutron beam in the Small Angle Neutron Scattering (SANS) facility at the Malaysian Nuclear Agency. PSD uses the 3 He(n, p) reaction to detect neutrons. Because of the 3 He high neutron cross section of 5333 b at 25.3 meV, a PSD is suitable for neutron detection across its axial direction at a low neutron flux of 10 3 cm −2 ‧s −1 . Because of its insensitivity toward gamma radiation, the signals from the PSD for real neutrons are relatively easy to analyze. This paper discusses the use of a PSD in neutron tomography and nanostructural characterization of material in the SANS facility at the Malaysian Nuclear Agency.